Drying characteristics and impacts on quality of marine Chlorella sp. biomass and extracts for fuel applications. Issue 6 (December 2021) - Amin, Muhammad; Chetpattananondh, Pakamas; Cheng, Chin-Kui; Sami, Syed Kamran; Khan, Muhammad Najam
Abstract: Drying is a crucial step in the processing of algae as it influences the biomass quality and economy of the process. Characteristics of solar drying (SD), oven drying (OD), and freeze drying (FD) of marine Chlorella sp. were studied. To reach a final moisture content below 10% it took 24, 23 and 72 h for FD at −50 ºC, OD at 80 °C and SD at 25–58 °C, respectively. Drying kinetics for SD and OD were best described by the Prakash and Kumar model. Protein and ash contents or elemental composition (CHN) of the biomass were not significantly affected by the choice of drying method. The highest lipid content was obtained in FD biomass (10.7%), followed by OD (5.2%) and SD (2.6%) cases. The SD, OD, and FD biomass samples were extracted by ultrasonication at 35 °C for 90 min using methanol/hexane (2:1 v/v). The extraction yields of SD, OD and FD biomasses were 22%, 27% and 31%, respectively. The free fatty acids in the extract from SD biomass were highest. The total chlorophylls (a and b) were 204.6, 159.7, and 137.2 µg/ml in the extracts from FD, OD, and SD cases. The drying method choice did not significantly affect degree of unsaturation, density, saponification value, iodine value, or cetane number, but did affect long chain saturation factor, cold filter pugging point, and oxidation stability. The extracts from FD, SD and OD biomasses could be good feedstocks for biofuel production and chlorophyll recovery for various applications is challenging. Graphical Abstract: ga1 Highlights: Drying of Chlorella sp. is vital to preserve its constituents for fuel production. Effects of drying methods on compositions of biomass and extract were studied. The extraction yield of SD, OD and FD biomasses were 22%, 27% and 31%, respectively. The total chlorophylls were 204.6, 159.7, and 137.2 µg/ml in FD, OD, and SD extracts. Drying methods had effects on cold filter plugging point and oxidation stability.